Delirium is one of the many faces of COVID-19. Literature review - Bagdonaitė , A.; Tumas , D.; Griškevičiūtė , E.; Svirskytė , A. (Neurologijos seminarai, 2020)
Taking into account today’s context of COVID-19 disease, it is very important to acknowledge the serious psychiatric complications that arise during the acute phase of the disease, as well as those that have a delayed onset and are no less dangerous. COVID-19 is most commonly associated with cough, shortness of breath, and fever; however, changes in consciousness can also occur, especially in elderly patients with severely advanced dis- ease. COVID-19 recovered patients often experience symptomatic mental disorders. The purpose of this article is to review the recent literature on COVID-19 induced delirium, its epidemiology, pathophysiological mechanisms, prevention, diagnostic and treatment options. The expectation is that this would help maintain clinical vigilance of healthcare professionals working during the global pandemic. Mention should also be made of the delayed-onset symptomatic psychiatric disorders that occur after recovery from COVID-19 disease, which are also important to recognize and treat in a timely manner, as they impair patients’ quality of life and the course of rehabilitation.
Keywords: delirium; COVID-19; delayed-onset psychiatric complications; antipsychotic; melatonin; valproic acid; symptomatic mental disorders